Larsen, M. (2014). Pensamiento innovador en Educación Comparada. Homenaje a Robert Cowen (Madrid: UNED). Recensión a cargo de Mª Jesús Martínez Usarralde - Martínez Usarralde, María Jesús (Revista Española de Educación Comparada, 2016)
Larsen, M. (2014). Pensamiento innovador en Educación Comparada. Homenaje a Robert Cowen (Madrid: UNED). Recensión a cargo de Mª Jesús Martínez Usarralde.